Mining and Peasant Societies Resistance: Political Ecology Perspective - Upe, Ambo (International Journal of Psychosocial Rehabilitation, 2020)
The exploitation of mining resources in various regions in Indonesia often has environmental, social, and economic impacts. These problems underlie the societies’ rejection of the surrounding mining activities. Likewise, the resistance of peasant societies in the Konawe Kepulauan Regency was vociferously voiced from 2015 to 2019. On this basis, this article aims to analyze the dynamics, strategies, and rationality of the resistance of peasant societies in the Konawe Kepulauan Regency. Methodologically, the research approach used in this study is a qualitative approach through discourse analysis. Data was collected by various news in the mass media from 2015 to 2019. Based on the results of the study it can be concluded two basic things. First, the dynamics of the resistance of the peasant society shows the pattern of daily resistance by involving a coalition of civil society as its strategy. Resistance is carried out in the form of joint demonstrations by unity student action and through advocacy by legal aid agencies. Second, the rationality of the resistance of the peasant societies in the Konawe Kepulauan Regency reflects the socio-ecological and socio-juridical rationality based on the ethics of subsistence by the principle of safety first.